Role of institutional ownership in moderating profitability and board of directors on sustainability report disclosure (Lighthouse Publishing, 2023)
Sustainability report disclosure is one of the important reports prepared by a company to provide information about company’s activities in relation to economic, environmental and social activities where the preparation of a sustainability report disclosure refers to the GRI Standards. Sustainability report disclosure helps the stakeholders and investors asses the company’s performance and helps them make decisions to create a sustainable development. This research aims to test the effect of profitability and the board of directors on sustainability report disclosure with institutional ownership as a moderating variable. This is classified as causal research with a quantitative approach. The population used is companies indexed by Kompas 100 in the Indonesia Stock Exchange period 2019-2021, and this research uses 60 samples. The hypothesis testing techniques are multiple regression analysis and moderated regression analysis with E-views 10. The results of this research prove that profitability has a significant positive effect on sustainability report disclosure, board of directors has no significant effect on sustainability report disclosure, and institutional ownership is unable to moderate the effect of profitability and board of directors on the sustainability report disclosure.